Restorative Justice for Child Maltreatment Victims: Transforming Crime Enforcement in Batam City - Fraiskam, Natasha; Sudirman, Lu; Shahrullah, Rina Shahriyani (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
Maltreatment of children, a persistent issue in Indonesia, including Batam City, often manifests through physical, emotional, or sexual abuse in households, schools, and public spaces. Such crimes cause profound psychological and physical harm, highlighting the urgent need for effective solutions. This study explores the application of restorative justice in handling child maltreatment cases in Batam City, emphasizing its future-oriented accountability, discussion-based negotiation, and healing-focused approach. Employing an empirical legal and social methodology, the research incorporates primary data through in-depth interviews with stakeholders, including prosecutors, police, victims, and relevant agencies, and secondary data from legal documents, books, and scientific publications. Findings reveal that while Batam’s law enforcement supports restorative justice, challenges and differing perspectives persist. This research contributes by proposing restorative justice as a progressive strategy to address child maltreatment, aiming for long-term benefits for victims, perpetrators, and society.